HUBUNGAN POLA ASUH DENGAN STATUS GIZI ANAK BALITA DI DESA BONGOMEME KECAMATAN DUNGALIO KABUPATEN GORONTALO - Talibo, Sofyawati; Tuna, Sri Yolanda (JOURNAL HEALTH AND NUTRITIONS, 2016)
ABSTRACT Nutritional problems are influenced by many factors that influence each other in a complex manner. At the household level, the state of nutrition is influenced by the ability of households to provide sufficient quantities and types of food and parenting styles that are influenced by educational, behavioral and household health factors. One of the causes of malnutrition in children under five is due to inadequate parenting (Tomayahu 2011 in Soekirman 2000).This study aims to determine the relationship between parenting and nutritional status of children under five in Bongomeme Village, Dungaliyo District, Gorontalo Regency.This study includes the type of analytic research. Populassi as many as 109 people, the sample is 86 people. Free variables are parenting and the dependent variable is the nutritional status of children under five. Data analysis in this study used the "chi square" statistical test.The results of this study found parenting of 44 people (51.16%) and those with good nutritional status amounted to 49 people (56.98%). The results of data analysis are based on the Chi square test of the square of the value of X2 calculated greater than X2 table (4,615> 3,481) then the alternative hypothesis is accepted and the null hypothesis is rejected.The conclusion of the study is that there is a relationship between the habit of parenting and nutritional status of children under five in Bongomeme Village, Dungaliyo District, Gorontalo Regency. ABSTRAK Masalah gizi dipengaruhi oleh banyak factor yang saling mempengaruhi secara kompleks. Ditingkat rumah tangga, keadaan gizi dipengaruhi oleh kemampuan rumah tangga menyediakan pangan dalam jumlah dan jenis cukup serta pola asuh yang dipengaruhi oleh factor pendidikan, perilaku dan keadaan kesehatan rumah tangga. Salah satu penyebab timbulnya kurang gizi pada anak balita adalah akibat pola asuh anak yang kurang memadai (Tomayahu 2011 dalam Soekirman 2000).Penelitian ini bertujuan untuk mengetahui hubungan pola asuh dengan status gizi anak balita di Desa Bongomeme Kecamatan Dungaliyo Kabupaten Gorontalo.Penelitian ini termasuk jenis penelitian analitik. Populassi sebanyak 109 orang, yang dijadikan sampel adalah 86 orang. Variable bebas yaitu pola asuh dan variable terikat adalah status gizi anak balita. Analisis data pada penelitian ini menggunakan uji statistic â€œchi squareâ€.Hasil penelitian ini didapatkan pola asuh berjumlah 44 orang (51,16%) dan yang berstatus gizi baik berjumlah 49 orang (56,98%). Hasil analisis data berdasarkan uji statistic Chi kuadrat nila X2 hitung lebih besar dari X2 tabel (4,615>3,481) maka hipotesis alternative diterima dan hipotesis nol ditolak.Kesimpulan penelitian adalah terdapat hubungan antara kebiasaan pola asuh dengan status gizi anak balita di Desa Bongomeme Kecamatan Dungaliyo Kabupaten Gorontalo.